Malaysian Cyberbullying Law: A Work-in-Progress - Mohamad, Ani Munirah; Abd Aziz, Ahmad Shamsul; Mohd Noor, Nor Azlina; Md Isa @ Yusuff, Yusramizza; Ibrahim, Huda; Ghazali, Osman (Malaysian Communications and Multimedia Commission (MCMC), 2014)
In Malaysia, cyberbullying cases are on the rise without any specific legal sanctions to manage them. Cyberbullying should be addressed so that its most harmful consequences such as suicide, theft, and rape can be prevented. Despite the grievous ramifications, existing laws are inadequate to manage cyberbullying matters. Hence, this research aims to break new ground in the existing literature by analysing the adequacy of Malaysian law in addressing cyberbullying as well as considering other jurisdictions’ experiences through the adoption of comparative analysis. This research investigated the relevant crucial aspects of existing and potential modalities to deal with cyberbullying that are frequently overlooked. By employing both qualitative and quantitative research methodologies, data was collected using library-based research, field work and online survey. Interviews were conducted with 19 cyberlaw experts and practitioners while an online survey was administered in which 120 respondents from the general public participated. The research findings have indicated that there is no specific law to manage cyberbullying in Malaysia. As it stands, there are laws that potentially cover cyberbullying, albeit not specifically referring to cyberbullying. In the international context, it has been evident from findings of the present study that the international instruments are generally not binding upon Malaysia. The study therefore proposes the creation of a stand-alone law to manage traditional bullying and cyberbullying. Additionally, the study also recommends alternative governing modalities for dealing with cyberbullying at different stages.